2021
DOI: 10.1007/s00068-021-01843-5
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde tibial nailing of far distal tibia fractures: a biomechanical evaluation of double- versus triple-distal interlocking

Abstract: Objectives Retrograde tibial nailing using the Distal Tibia Nail (DTN) is a novel surgical option in the treatment of distal tibial fracture. Its unique retrograde insertion increases the range of surgical options in far distal fractures of the tibia beyond the use of plating. The aim of this study was to assess the feasibility of the DTN for far distal tibia fractures where only double rather than triple-distal locking is possible due to fracture localisation and morphology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The torsion test, which measures the torsional resistance of internal fixation devices, is a commonly used biomechanical performance test for lower limb fracture fixation. Greenfield et al conducted torsional biomechanical testing on RTN and found that both triple screw locking and double screw locking demonstrated good torsional resistance capabilities ( Greenfield et al, 2022 ) In a biomechanical comparison study conducted by Kuhn et al between RTN and minimally invasive percutaneous plates, the results showed that RTN exhibited better stability in both clockwise and counterclockwise torsion ( Kuhn et al, 2014a ). The findings of this study are consistent with the aforementioned research, where RTN demonstrated superior torsional resistance performance compared to distal tibia plates at torque levels of 4 N m and 5 N m. According to the author’s analysis, the RTN used in this study employed triple screw locking at the distal end and double screw locking at the proximal end, which contributed to its ability to resist torsional forces effectively, thus providing greater stability to the fracture site.…”
Section: Discussionmentioning
confidence: 99%
“…The torsion test, which measures the torsional resistance of internal fixation devices, is a commonly used biomechanical performance test for lower limb fracture fixation. Greenfield et al conducted torsional biomechanical testing on RTN and found that both triple screw locking and double screw locking demonstrated good torsional resistance capabilities ( Greenfield et al, 2022 ) In a biomechanical comparison study conducted by Kuhn et al between RTN and minimally invasive percutaneous plates, the results showed that RTN exhibited better stability in both clockwise and counterclockwise torsion ( Kuhn et al, 2014a ). The findings of this study are consistent with the aforementioned research, where RTN demonstrated superior torsional resistance performance compared to distal tibia plates at torque levels of 4 N m and 5 N m. According to the author’s analysis, the RTN used in this study employed triple screw locking at the distal end and double screw locking at the proximal end, which contributed to its ability to resist torsional forces effectively, thus providing greater stability to the fracture site.…”
Section: Discussionmentioning
confidence: 99%
“…Greenfeld et al established that double locking preserved compressive stiffness by 60% to 70% and torsional stiffness by 90% compared to triple locking in retrograde tibia nailing. [26] Thus, the IMN with a distal double locking can be considered for far distal tibia fractures where nailing is preferred over plating. Accordingly, we found similar displacement values in single and cyclic tests at all 3 fracture levels fixed with 2 distal locking screws.…”
Section: Discussionmentioning
confidence: 99%